Alcoholic beverages. Volume 7, The science of beverages / Alexandru Mihai Grumezescu; Alina Maria Holban - Grumezescu, Alexandru Mihaiedited by
Alcoholic Beverages, Volume Seven in The Science of Beverages series, is a multidisciplinary resource for anyone who needs deeper knowledge on the most recent approaches in beverage development, technology, and engineering, along with their effects on beverage composition, quality, sensory and nutritional features. The book discusses main alcoholic beverages, such as spirits and wines that are thoroughly analyzed in terms of production, sustainability, and future perspectives. It offers examples of the new trends and the most recent technologies and approaches in the industry of alcoholic drinks.